2021
DOI: 10.3390/nu13082804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Food Components on Cognitive Functions in Older Adults

Abstract: Population aging has recently been an important issue as the number of elderly people is growing worldwide every year, and the extension of social security costs is financially costly. The increase in the number of elderly people with cognitive decline is a serious problem related to the aging of populations. Therefore, it is necessary to consider not only physical care but also cognitive patterns in the future care of older adults. Since food contains a variety of bioactive substances, dietary patterns may he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 214 publications
(260 reference statements)
0
22
0
2
Order By: Relevance
“…For example, it has been found that polyamine, lysine, and tryptophan metabolism, and glycine and valine levels are altered in blood samples across AD, MCI, and CN groups (67,68). Various studies have also explored the role of amino acid intake in the progression of AD; however, most research is still speculative due to the lack of specific underlying mechanisms (69). Our study found that decreased levels of arginine and serine are associated with AD and MCI progression in brain component 2 , and decreased levels of asparagine, methionine, and threonine are associated with MCI progression in brain component 3 in men but not women.…”
Section: Amino Acids Sex Differences In Admentioning
confidence: 99%
“…For example, it has been found that polyamine, lysine, and tryptophan metabolism, and glycine and valine levels are altered in blood samples across AD, MCI, and CN groups (67,68). Various studies have also explored the role of amino acid intake in the progression of AD; however, most research is still speculative due to the lack of specific underlying mechanisms (69). Our study found that decreased levels of arginine and serine are associated with AD and MCI progression in brain component 2 , and decreased levels of asparagine, methionine, and threonine are associated with MCI progression in brain component 3 in men but not women.…”
Section: Amino Acids Sex Differences In Admentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (n-3 PUFAs), such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) obtained from diet or dietary supplements [3,4], have been reported to have beneficial neurological effects by improving cognitive performance [5][6][7][8] in neurodegenerative disorders and depression [9,10]. Recently, DHA and EPA were reported to promote BBB integrity in a sample of healthy elderly (mean age 76 yrs) human subjects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is mandatory to find more efficacious preventive strategies to straightly prevent, decelerate, and even discontinue this “dementia pandemic.” Physical exercise and healthy dietary habits have been identified as some of the most efficient therapeutic approaches and are recommended from early life ( Blumenthal et al, 2017 ). In addition, the connection between diet, health, and the presence of bioactive chemical compounds in food has gotten fantastic attention in recent years and consumers are progressively interested in food products that, apart from fulfilling nutritional demands, enhance physical performance, further wellbeing, and reduce the risk of producing diseases ( Auxtero et al, 2021 ; Ozawa et al, 2021 ). Nutritional interventions or botanicals such as polyphenols can be a greatly accepted, inexpensive, and efficacious option to preserve against age-related cognitive decline and neurodegeneration, leading to important personal and societal benefits ( Tewari et al, 2018 ; de Araujo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%